Reconstructing The Sharia Economic Integration Model: A Path Toward Santri Economic Independence in The Pesantren Context - Abdul Chamid; Emiola Habeeb Olasunkanm; Habeebullah Abdus-salaam (LPPPM STAI Darul Hikmah Bangkalan, 2026)
This study examines an integration model of Islamic economics into the curriculum of Islamic boarding schools (pesantren) as an effort to strengthen students’ economic independence. Although many pesantren conduct economic activities and teach fiqh muamalah, these elements often operate without systematic curriculum reconstruction. Using a qualitative case study approach, data were collected through document analysis, participatory observation, and in-depth interviews with administrators, teachers, and students. Data were analyzed through open, axial, and selective coding to identify patterns of integration and structural gaps. The findings reveal that integration occurs across three operational dimensions: (1) textual–normative instruction through classical fiqh muamalah texts, (2) structured economic practices via student business unit rotations, and (3) institutionalized ethical supervision mechanisms. However, these dimensions remain fragmented and are not formally embedded into measurable curriculum structures. Based on these findings, this study reconstructs a Sharia Economic Curriculum Integration Model consisting of four interrelated components: value integration, formal curriculum integration, practice-based learning integration, and institutional economic ecosystem integration. The study concludes that integrating Islamic economics in pesantren is not merely the addition of economic content but requires epistemological restructuring of the curriculum to bridge classical religious scholarship and applied economic competence. This reconstruction strengthens the role of pesantren as institutions that cultivate both religious authority and sustainable economic independence.